1997
DOI: 10.1002/prep.19970220502
|View full text |Cite
|
Sign up to set email alerts
|

CL‐20 performance exceeds that of HMX and its sensitivity is moderate

Abstract: The explosive performance of ϵ‐CL‐20 was found to be approximately 14% greater than HMX as determined by cylinder expansion and tantalum plate acceleration experiments. This makes it the most powerful explosive ever tested at small volume expansions of the detonation products. In general CL‐20 is more sensitive than HMX. However, the sensitivity of CL‐20 to one‐dimensional shock loading was found to be similar to HMX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
290
0
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(307 citation statements)
references
References 6 publications
11
290
0
6
Order By: Relevance
“…7 However, CL-20 has not achieved widespread engineering applications because of relative high sensitivity to heat, friction, and shock. Recently, a 1 : 1 molar ratio co-crystal of TNT and CL-20 has been synthesized experimentally 8 that displays greatly reduced sensitivity compared to pure CL-20 while retaining the high performance due to the incorporation of TNT, a relative stable low-power explosive.…”
mentioning
confidence: 99%
“…7 However, CL-20 has not achieved widespread engineering applications because of relative high sensitivity to heat, friction, and shock. Recently, a 1 : 1 molar ratio co-crystal of TNT and CL-20 has been synthesized experimentally 8 that displays greatly reduced sensitivity compared to pure CL-20 while retaining the high performance due to the incorporation of TNT, a relative stable low-power explosive.…”
mentioning
confidence: 99%
“…先后成功设计合成出双环奥克托今(DCHMX)及其类似 物 [23,24] 、4,10-二硝基-2,6,8,12-四氧杂-4,10-二氮杂四环 [5.5.0.0.0]十二烷(TEX) [25,26] 、六硝基六氮杂异伍兹烷 (CL-20) [27,28] 、 1,1'-二羟基-3,3'-二硝基-5,5'-联-1,2,4-三唑 二羟胺盐(MAD-X1) [ …”
unclassified
“…CL-20, the most powerful high explosive, is being synthesized at the High Energy Materials Research Laboratory (HEMRL, Pune, India) by nitration of 2,6,8,4,6,8,10,. Nitration of TAIW is a mild exothermic reaction.…”
mentioning
confidence: 99%
“…In the present study it was found that for $85% yield, optimized temperature envelope was 72-85 C, nitric acid concentration range from 98 to 92%, reaction time was 1 h, and temperature during the addition of TAIW into the mixed acid was 25-40 C. In order to improve the particle size of CL-20, during the recrystallization process, the effect of parameters like addition rate of anti-solvent and rate of agitation were studied and Introduction CL-20, first synthesized by Nielsen [1], is the most energetic and futuristic high explosive. It is a potential candidate to replace HMX [2]. Balas et al [9] of the U.S. Army TACOM-ARDEC.…”
mentioning
confidence: 99%